Cebranopadol, a novel first‐in‐class drug candidate: Method validation and first exploratory pharmacokinetic study in rabbits. Issue 4 (25th January 2021) - Łebkowska‐Wieruszewska, Beata; Gbylik‐Sikorska, Małgorzata; Gajda, Anna; Sartini, Irene; Lisowski, Andrzej; Poapolathep, Amnart; Giorgi, Mario
Abstract: Cebranopadol is a novel, centrally acting, potent, first‐in‐class analgesic drug candidate with a unique mode of action that combines nociceptin/orphanin FQ peptide receptor and opioid peptide receptor agonism. The present study aimed to develop and validate a novel UHPLC‐MS/MS method to quantify cebranopadol in rabbit plasma and to assess its pharmacokinetics in rabbits after subcutaneous (s.c.) administration. Twelve adult females were administered with 200 µg/kg s.c. injection. Blood samples were withdrawn at 15, 30 and 45 min and 1, 1.5, 2, 4, 6, 8, 10 and 24 hr after administration. The plasma samples were extracted with a liquid/liquid extraction. The new analytical method complied with the EMA requirements for the bioanalytical method validation. The method was selective, repeatable, accurate, precise and robust with a lower limit of quantification of 0.1 ng/ml. In all the rabbits, cebranopadol was quantifiable from 0.25 to 10 hr. Mean Cmax and Tmax were 871 ng/ml and 0.25 hr, respectively. Further studies including the i.v. administration are necessary to fully evaluate the pharmacokinetic features of this novel active compound.